WHAT DID WE DO BETWEEN 1998-2012 IN TURKEY? A REVIEW OF THE RESEARCH ON NATURE OF SCIENCE - (:unkn) unknown (IATED-INT ASSOC TECHNOLOGY EDUCATION A& DEVELOPMENT, 2014)
During the past two decades, a significant body of research has focused on students' understandings of the nature of science (NOS). This situation motivated many countries all over the World to improve students' understandings of NOS through curriculum efforts and reform. Since 1998, Turkey has been studying about nature of science with undertaking efforts to reform pre-college education. The new Turkish national science education curriculum has emphasized that all students, regardless of individual and cultural differences, should develop scientific and technological literacy (Ministry of National Education [MONE], 2004 & 2013). This study investigates the extent to which curriculum effort is achieving on students and teachers views of NOS, using paper and master & PhD thesis which are published between 1998 & 2012 years in Turkey. For this purpose; 90 articles, 29 master and 15 PhD thesis accessed via the internet, are compared in detail in terms of topics, sample, methods and results through document analysis. The results indicate that, compared to 134 research, students of all grades, preservice and inservice teachers have not attained the desired understanding of NOS. This study shows that national science curriculum and teacher education programs, are insufficient of improving students' and teachers' views of NOS. The most important contribution of present study is reveal of professional development programs, and science education programs need to provide opportunities with content and pedagogical content knowledge for both in-service and pre-service science teachers reflect on their teaching practices instead of changing curriculum each seven years (MONE; 1998-2005-2013).
Keywords: Nature of Science; Science Education in Turkey; Science Curriculum; Professional Development Program